Pengaruh Profitabilitas, Solvabilitas, Umur Perusahaan, Fee Audit, dan Ukuran KAP Terhadap Audit Delay - Febriana, Devi; Wijaya, Rico; Jumaili, Salman (Politeknik Ganesha Medan, 2024)
This study aims to empirically prove the influence of profitability, solvency, company age, audit fees and size of the public accounting firm on audit delay. This research is quantitative research using secondary data obtained from company annual reports. The population in this research is non-cyclical consumer sector companies listed on the Indonesia Stock Exchange in 2019-2021. The number of samples used in this research was 135 data. The data analysis technique used is multiple linear regression analysis. Based on the results of the analysis, it is known that simultaneously the variables profitability, solvency, company age, audit fees and the size of the public accounting firm influence the audit. while partially the solvency variable has a significant effect on audit delay, while the variables profitability, company age, audit fees and KAP size partially have no effect on audit delay.